Olfaction in alcohol-dependence: a neglected yet promising research field - Maurage, Pierre; Rombaux, Philippe; De Timary, Philippe (Frontiers in Psychology, 2014)
Olfaction research deeply renewed the knowledge of the pathophysiological mechanisms involved in various psychopathological states and showed that olfactory deficits might constitute an onset or trait marker in psychiatry. However, while alcohol-dependence is the most wide spread psychiatric disorder and while olfaction might be involved in its development and maintenance, olfactory abilities have been little explored in this population. The central aim of this paper is thus to underline the usefulness of olfaction research in alcohol-dependence. After reviewing the few olfaction studies available, a research agenda will be proposed, identifying the major challenges for future research, and particularly: (1) the identification of the origin, extent and cerebral correlates of olfaction deficits; (2) the links between olfaction and emotional-cognitive deficits, and the use of olfaction to understand the pathomechanisms of alcohol-dependence; (3) the interactions between olfaction and other sensory modalities; (4) the use of olfaction to predict the appearance and intensity of cognitive impairments; (5) the impact of olfaction deficits on everyday life in alcohol-dependence.